Model questions and answers on law relating to banking (including tutorial notes) - Adeboye, T. O. (Ilorin, Kwara State [Nigeria] : Dabot Professional Books Productions, 1990)
The book elaborates on the legal implications of the banking business.
Spine title: Q & A, law relating to banking.
Cover title: Model questions & answers on law relating to banking (including tutorial notes).
rua 05/02/15
Loans
Keywords: Banking law -- Nigeria -- Miscellanea